FEM analysis of a DCP implant on a human femoral bone with a fracture gap - Fongsamootr,T. (2015)
Our research aims to determine the optimal screw configuration of a dynamic compressive plate (DCP) implant on a human femoral bone. The number of screws and the positioning are sensitive parameters of DCP implant stress repartition. Several previous studies have assessed the influence of thescrew configuration of a DCP implant. Using a realistic geometry of a human left femur and the finite element method (FEM), the calculations in those papers were based on a safe femoral bone. This study evaluates the influence of the application of a simulated fracture gap in the diaphyseal part on the stress repartition of the bone, plate, and screws. The main purpose is to complete the existing studies in order to provide surgeons with information on an optimal prosthesis screw configuration. The plate and screws were modeled and assembled on a cracked femoral bone. The hip region of the femur was loaded with vertical and horizontal forces. The femoral bone was cut into two parts because of the gap: the top part, close to thehip, and the bottom part, close to the knee. The FEM analysis shows that the stresses in screws located in the top part of the femoral bone had significantly increased, whereas the stresses on the plate and the bone had been reduced. Copyright © 2012 by ASTM International.